Mobile Telecommunications Protocols For Data Networks - Hac, Anna (John Wiley & Sons, 2011)
Mobile users are demanding fast and efficient ubiquitous connectivity supporting data applications. This connectivity has to be provided by various different networks and protocols which guarantee that mobile networks function efficiently, performing routing and handoff for mobile users.